The COVID-19 Healthcare Personnel Study (CHPS): Overview, Methods, and Preliminary Findings. Issue 1 (6th January 2022) - DiMaggio, Charles; Abramson, David; Susser, Ezra S.; Hoven, Christina W.; Chen, Qixuan; Andrews, Howard F.; Herman, Daniel; Kreniske, Jonah; Ryan, Megan; Susser, Ida; Thorpe, Lorna E.; Li, Guohua
Abstract : Introduction: The COVID-19 Healthcare Personnel Study (CHPS) was designed to assess adverse short-term and long-term physical and mental health impacts of the coronavirus disease-2019 (COVID-19) pandemic on New York's physicians, nurse practitioners, and physician assistants. Methods: Online population-based survey. Survey-weighted descriptive results, frequencies, proportions, and means, with 95% confidence intervals (95% CI). Odds ratios (ORs) for association. Results: Over half (51.5%; 95% CI: 49.1, 54.0) of respondents worked directly with COVID-19 patients; 27.3% (95% CI: 22.5, 32.2) tested positive. The majority (57.6%; 95% CI: 55.2, 60.0) reported a negative impact on their mental health. Negative mental health was associated with COVID-19 symptoms (OR=1.7, 95% CI: 1.3, 2.1) and redeployment to unfamiliar functions (OR=1.3, 95% CI: 1.1, 1.6). Conclusions: A majority of New York health care providers treated COVID-19 patients and reported a negative impact on their mental health.